Test results of a superconducting FCL using bifilar coil of BSCCO-2212 - Baldan, Carlos A.; Shigue, Carlos Y.; Figueira, Domingos S. S.; Ruppert Filho, Ernesto; Freitas, Rafael C. (Institute of Electrical and Electronics Engineers (IEEE), 2006)
A single-phase superconducting Fault Current Limiter using a bifilar coil of BSCCO-2212 tube was tested in 220 V-60 Hz line during fault current between 1 kA to 4 kA, operating in 77 K. In this work are presented the critical current dependence as a function of an external magnetic field applied and the results can be used to predict the current limiter performance. The experimental setup is described and the test results are presented for the unit conducting a steady nominal AC current of 200 A, and also during the fault time (1 to 6 cycles). The performance of the bifilar coil to provide the limiting impedance associated with the dynamic resistance developed during the beginning of the fault was analyzed and compared with other types of superconducting current limiters.
Keywords: HTS coils; HTS tube; superconducting fault current limiter